Efficacy and safety of olaparib in advanced ovarian cancer: a meta-analysis. (31st December 2023) - Yang, Yuanyuan; Yang, Xiaoyun; Li, Huaifang; Tong, Xiaowen; Zhu, Xinxian
Abstract: This study aimed to evaluate the efficacy and safety of olaparib for the treatment of advanced ovarian cancer. All studies that assessed the efficacy and safety of olaparib in advanced ovarian cancer were searched in PubMed, Embase, and Web of Science from their inception to 20 September 2022. The analysis included six studies and 2016 patients. Olaparib could significantly prolong the progression-free survival (PFS) of patients compared to that of the control group (HR = 0.49, 95% CI = 0.36 − 0.68). However, no statistically significant differences were detected in overall survival (OS) and objective response rate (ORR) between the olaparib and control groups. Olaparib treatment increased the number of grade ≥3 adverse events (AEs) in patients with advanced ovarian cancer compared with that in the control group. Olaparib significantly prolonged PFS in patients with advanced ovarian cancer; however, no statistically significant differences were detected in OS and ORR. In terms of safety, olaparib has manageable adverse effects.